Tinjauan Hukum Ekonomi Syariah Terhadap Kerjasama Muzara’ah Dalam Pengelolaan Lahan Pertanian - Ratna Dewi; Zainuddin Zainuddin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to review sharia economic law on muzara'ah cooperation in the management of agricultural land in Jorong Sungai Tarab, Tanah District. This research is a qualitative descriptive research. The data used in this research are primary data in the form of direct interviews with 6 informants. The data analysis method used is the Miles and Huberman model which consists of the data analysis process, data reduction, data selection and data validity. This study examines the implementation of muzara'ah in the management of agricultural land in Jorong Sungai Tarab, Tanah Datar Regency. The results of this study explain that in general the implementation of muzara'ah cooperation on agricultural land in Jorong Sungai Tarab, Tanah Datar Regency is already in accordance with sharia economic law, this can be seen from the fulfillment of the pillars and conditions of cooperation starting from land owners, land cultivators, land to be worked on and sighat contract